Upaya Memutus Rantai Penyebaran COVID-19 melalui Penyuluhan Pentingnya Penggunaan Masker di Masa Pandemi - Yusuf, Rezky Aulia; Yunus, Inayah Ilmiah; Amir, Haeril; Hidayat, Rahmat (PT.Mantaya Idea Batara, 2023)
The increase on COVID-19 cases that occur in the community is supported by a fast virus transmission process, in dealing with the spread of Covid-19, it is necessary to carry out preventive efforts in the community. Wearing a mask is an effort to break the chain of the spread of Covid-19. The purpose of this community service is to increase public knowledge in RT 001 regarding the importance of using masks in the Covid-19 pandemic era. This community service was carried out by providing education through counseling using LCD and powerpoint media, and evaluation was carried out in the form of pretest and posttest with questionnaires, accompanied by the distribution of masks and vitamin C. From the counseling carried out there was an increase in knowledge after the intervention. in the form of counseling. With this intervention, it is hoped that the community can implement the knowledge they now have in their daily lives, in particular to continue to apply the health protocol, namely by using a mask when traveling to avoid the spread of the corona virus.